2016
DOI: 10.1186/s12711-016-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction using preselected DNA variants from a GWAS with whole-genome sequence data in Holstein–Friesian cattle

Abstract: BackgroundWhole-genome sequence data is expected to capture genetic variation more completely than common genotyping panels. Our objective was to compare the proportion of variance explained and the accuracy of genomic prediction by using imputed sequence data or preselected SNPs from a genome-wide association study (GWAS) with imputed whole-genome sequence data.MethodsPhenotypes were available for 5503 Holstein–Friesian bulls. Genotypes were imputed up to whole-genome sequence (13,789,029 segregating DNA vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
121
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 40 publications
20
121
3
Order By: Relevance
“…We found that using S_GWAS did not improve the prediction accuracy values, especially for p-value cutoffs less than 0.001 (Table 2). Similar results were also indicated in previous studies using SNPs preselected from GWAS (Veerkamp et al, 2016;Ye et al, 2019). The main reason for this result is that overfitting decreases the prediction accuracy.…”
Section: Snp Preselection Strategies Influencing Prediction Accuracysupporting
confidence: 90%
See 1 more Smart Citation
“…We found that using S_GWAS did not improve the prediction accuracy values, especially for p-value cutoffs less than 0.001 (Table 2). Similar results were also indicated in previous studies using SNPs preselected from GWAS (Veerkamp et al, 2016;Ye et al, 2019). The main reason for this result is that overfitting decreases the prediction accuracy.…”
Section: Snp Preselection Strategies Influencing Prediction Accuracysupporting
confidence: 90%
“…Therefore, pre-selected potential causal markers or QTLs from WGS are necessary for improving the accuracy of genomic prediction (Raymond et al, 2018). Thus, many preselection variant strategies were used to improve the power of genomic prediction based on the following methods: genomewide association study (GWAS) (Zhang et al, 2014;Veerkamp et al, 2016;Song et al, 2019;Ye et al, 2019), Bayesian procedures (Kemper et al, 2015), genome-wide signatures of selection (Ye et al, 2020), Animal QTLdb (Song et al, 2019), gene annotation (Heidaritabar et al, 2016;Gao et al, 2017), and gene ontology categories (Edwards et al, 2016;Abdollahiarpanahi et al, 2017). These methods mainly depend on the direct link between phenotype and DNA variants or some prior genome annotation information.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of 35 genomic selection and the power of genome wide association studies depend on both the number 36 of individuals that have genomic data and its density (e.g., Daetwyler et al, 2008;Hayes et al, 37 2009; Hickey et al, 2014; Gorjanc et al, 2015) . The goal is then to generate genomic data on as 38 many individuals as possible at as high of a density as possible with the upper limit being the 39 presence of whole genome sequence on hundreds of thousands or millions of individuals (Hickey,40 2013; Daetwyler et al, 2014;Veerkamp et al, 2016). 41…”
Section: Abstract 12mentioning
confidence: 99%
“…However, when the number of imputed variants was reduced, and those were selected based on association with the trait, then the peaks eventually were found (Calus et al, 2016). Similar, when single SNP testing was applied (Veerkamp et al, 2016) in the same data, clearer QTL peaks were identified when using sequence data in comparison with SNP array data. Other studies showed that a multi-breed population results in more precise QTL mapping than a single breed population (Raven et al, 2014;Kemper et al, 2015).…”
Section: Qtl Detectionmentioning
confidence: 97%
“…Pre-selection can be performed by first performing a GWAS and select the SNPs with the lowest p-values for genomic prediction. Veerkamp et al (2016) investigated this approach, but did not find a clear benefit of using whole-genome sequence data for genomic prediction using the same data as used in Chapter 4.…”
Section: Genomic Predictionmentioning
confidence: 99%